2014
DOI: 10.1902/jop.2013.130356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Therapy on Metabolic and Inflammatory Parameters of Rats With Ligature‐Induced Periodontitis Associated With Restraint Stress

Abstract: Based on the methodology used, PT may reduce tissue breakdown resulting from PD in unstressed rats. The protocol used for restraint stress influenced the immunomodulatory effects of PT in intestinal and periodontal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 49 publications
6
48
0
3
Order By: Relevance
“…Our findings are corroborated by previous research that verifies the beneficial effects of probiotic use in periodontal treatment in animals and supports the beneficial clinical results of probiotic use on different conditions, such as reduction in the numbers of periodontopathogens and inflammatory cytokines , in the degree of gingival inflammation and of chronic periodontitis . It also draws attention to its possible use in locations where the scaling and root planing procedure cannot be performed, such as hospital clinics.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are corroborated by previous research that verifies the beneficial effects of probiotic use in periodontal treatment in animals and supports the beneficial clinical results of probiotic use on different conditions, such as reduction in the numbers of periodontopathogens and inflammatory cytokines , in the degree of gingival inflammation and of chronic periodontitis . It also draws attention to its possible use in locations where the scaling and root planing procedure cannot be performed, such as hospital clinics.…”
Section: Discussionsupporting
confidence: 89%
“…Oral administration of Bacillus subtilis reduced rat alveolar bone loss induced by ligature-induced periodontitis and also protected rats from small intestinal changes induced by periodontal inflammation(57). Stress was identified to influence the extent of the effect of probiotic therapy in periodontitis models (58), such that effects of the probiotic ( B. subtilis ) are less effective in the presence of stress. In another periodontal study, oral Saccharomyces cerevisiae was used as a monotherapy or combined as an adjuvant with standard therapy, and in both cases led to effective repair processes including less alveolar bone loss, decreased pro-inflammatory cytokines TNFα and IL1β and increased anti-inflammatory cytokine IL-10 (59).…”
Section: Introductionmentioning
confidence: 99%
“…The above studies 12‐14,17‐19 indicate that the changes observed in the serum RANKL/OPG system in CP or T2DM are still unclear. Considering the bidirectional relationship between CP and T2DM and the immuno‐inflammatory function of the RANKL/OPG system, it would be interesting to observe the characteristics of these biomarkers in serum in patients with CP and T2DM and the potential effect of periodontal intervention.…”
mentioning
confidence: 99%
“…OPG, a glycoprotein and a member of the tumor necrosis factor receptor superfamily, acts as a soluble decoy receptor and blocks the binding of RANKL to RANK, thus preventing osteoclastogenesis 11 . Some investigations showed that, as RANKL levels increase, OPG levels decrease, and the R/O ratio increases in the gingival crevicular fluid (GCF) and serum in patients with periodontitis and experimental periodontitis 12–14 …”
mentioning
confidence: 99%